2000
DOI: 10.1046/j.1440-1746.2000.02205.x
|View full text |Cite
|
Sign up to set email alerts
|

Branched‐chain amino acids

Abstract: The branched‐chain amino acids (BCAA), isoleucine, leucine and valine, are unique in that they are principally metabolized extrahepatically in the skeletal muscle. This observation led to the investigation of these nutrients in a number of clinical scenarios. By far the most intensively studied applications for BCAA have been in patients with liver failure and/or patients in catabolic disease states. However, the resulting studies have not demonstrated a clear clinical benefit for BCAA nutritional supplements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(85 citation statements)
references
References 95 publications
0
77
0
4
Order By: Relevance
“…Studies evidenced that intravenous leucine infusion at high doses (3 to 7 g) resulted in anabolic changes in protein turnover and nitrogen balance (Platell et al, 2000;Matthews, 2005). Additionally, it was observed that leucine stimulates protein synthesis during catabolic conditions induced by acute food restriction or by exhaustive exercise (Donato et al, 2007;Biolo et al, 1997).…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Studies evidenced that intravenous leucine infusion at high doses (3 to 7 g) resulted in anabolic changes in protein turnover and nitrogen balance (Platell et al, 2000;Matthews, 2005). Additionally, it was observed that leucine stimulates protein synthesis during catabolic conditions induced by acute food restriction or by exhaustive exercise (Donato et al, 2007;Biolo et al, 1997).…”
Section: Experimental Studiesmentioning
confidence: 99%
“…During prolonged endurance exercise, the oxidation of BCAA is increased several-fold ( 16 ). In contrast to other amino acids, BCAA are unique in that they are principally metabolize extrahepatically in the skeletal muscle tissue ( 17 ). The oral intake of BCAA might have beneficial effects on skeletal muscle in the state of an impaired renal function.…”
mentioning
confidence: 99%
“…Supplementation of glutamine may improve protein status and immunocompetence, enhance nutritional management, reduce the number of infections and augment recovery of the seriously ill while minimizing hospital stay 30,32,[34][35][36][37] . Leucin stimulates skeletal muscle protein synthesis and inhibits muscle proteolysis, even during sepsis 5,56,57 . The prevalent opinion in modern critical care nutrition is that 1.2-1.5 g protein/kg normal body weight/day is sufficient and hence not usually exceeded.…”
Section: Resultsmentioning
confidence: 99%
“…Leucine also stimulates skeletal muscle protein synthesis and inhibits muscle proteolysis -even during sepsis 5,56,57 . Plasma concentrations of the BCAA are more prominently affected than the concentrations of other amino acids by changes in dietary-caloric, protein, fat, and carbohydrate-intake in man 58 .…”
Section: Branched-chain Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation